TINJAUAN KONSEP DESAIN FLATPACK PADA RAK SUSUN 5 TINGKAT TERBUKA MASTERSPACE HOLELESS - Rizky Dinata; Marwan Noer (Universitas Mercu Buana, 2020)
The success of developing new products is a prerequisite for companies to remain competitive in a market that is always demanding. The design concept with the term Flat-pack became very popular and inspired the design of other products, especially product design in small industries or artisans in Indonesia. Research on producing products that have successfully applied this design concept is very much needed to review and discuss the product details of the holeless level 5 Masterspace Rak as a product that will be a case study of how the design process and success in applying the Flat-pack design concept, with the basic principles of knockdown and RTA Ready theory To Assemble. The method that will be used to achieve the objectives of this research is the Basic Theory Method. In carrying out this method, it will be sought where phenomena can be said to be core phenomena that can be taken and formed into a theory. It is hoped that through this research, the results can be applied to the planning of craft innovative products by small craftsmen while still being able to compete globally.